Study the Inhibitory effect of Rose and blossom bitter orange flowers extracts against different types of bacteria isolated from the oral cavity (Baghdad Science Journal, 2025)
The study in duded isolation and identification of microbial isolates from oral cavity to 10 volunteers, diagnosed within the three groups: Staphylococcus aureus, Staphylococcus epidermidis, Streptococcus spp. and Candida albicans . The sensitivity test of all isolates bacteria Streptococcus spp. , S. aureus and S. epidermidis showed high resistance to Ampicillin(100)%,followed Methicillin (88.88)% and Amoxicillin / clavulanic acid(77.77)%, while the resistance for each of Vancomycin and Amoxicillin were (66.66)%, and the resistance to Erythromycin and Pencillin (55.55)% to each of them. The results showed less resistance to Trimethoprim (22.22)% and Cefalotine (11.11)% of all bacteria isolate. Investigation of the presence of active compounds in each of the hot and cold (water and alcoholic) extracts flowers Rose and flowers blossom bitter orange ( new preparatory 2012) (Alkaloids, Quartet alkaloids, sugars, Saponine, Flavones and comarins ) was carried out includes. While it was all kinds of extracts does not contain resins. The results showed the presence of active compounds (Sugars, Flavones and comarins) in old extracts that preparation after a year (2011). PH values of the plant extracts hot and cold (water and alcoholic) for each of orange flowers blossom and Rose flowers (Old and new preparatory) with a wide range ranging between (3.6 -6.4). All extracts hot and cold (alcoholic) (new preparatory 2012) showed most effective towards Streptococcus spp., S. epidermidis and Candida albicans, while the extracts show weak effective against S. aureus. Hot alcohol extracts of Rose (old preparatory 2011) showed most effective towards S. aureus and S. epidermidis only, while the other extracts of old perpetration show weak effective against Streptococcus spp. and C. albicans.